Hydrogen Bond Dynamics of Water-Acetone Mixtures Studied by The Complex Permittivity - Hai Yan, Tang (Asian Journal of Chemistry, 2012)
The complex permittivity of water-acetone mixtures, over the entire concentration range, have been measured using the resonant cavity perturbation method at 298 K. It was noticed that the permittivity gradually decreased with increasing concentration of acetone in water, whereas the relaxation time decreased with increasing concentration and temperature. The observed values of the dielectric parameters confirm that H-bonded molecular interactions decrease the number of effective parallel aligned dipoles with the formation of complexes in water-acetone mixtures.